Utilization of Fermented Turi Leaf (Sesbania grandiflora) Meal WithTrichoderma sp. As Feed Ingredients to Increase on The Growth Of Green Catfish (Hemibagrus nemurus) Fingerlings - Febrico Febrico; Adelina Adelina; Indra Suharman (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2019)
ABSTRACTThe research was conducted for 56 days , the aim to determine the effect and get the percentage fermented turi leaf (Sesbania grandiflora) Meal with Trichoderma sp. in feed on feed efficiency. This study uses completely randomized design (CRD) with one factor, with 5 treatment levels and 3 repetitions. The test feed used in this study was artificial feed with a protein content of 35% with a percentage Utilization of FTLM namely 0%, 5%, 10%, 15% and 20%. Test feed given as much as 10% of the weight of biomass per day with the frequency of feeding three times throughout the day is at 08.00, 12.00 and 16.00. The fish used in this research with in 0,99 g of weight. Fish were reaered in 15 cage units (0,5x0,5x1 m3) with the stocking density of 20 fish/m3. The results showed that the percentage of FTLM significant effect (P<0,05) on feed efficiency, protein retention and specific growth rate but did not significantly affect the survival rate of green catfish fingerlings. Based on the results of this study concluded that Utilization of FTLM 10% give the best respons on the feed efficiency 43,08%, protein retention 30,10%, specific growth rate 3,86% and survival rate 96,67%. Keywords : Fermented Turi Leaf Meal, Hemibagrus nemurus, Growth, Trichoderma sp.